2020
DOI: 10.3390/cryst10030218
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electrodeposition for Copper Nanowires

Abstract: Copper nanowires (Cu NWs) are a promising alternative to indium tin oxide (ITO), for use as transparent conductors that exhibit comparable performance at a lower cost. Furthermore, Cu NWs are flexible, a property not possessed by ITO. However, the Cu NW-based transparent electrode has a reddish color and tends to deteriorate in ambient conditions due to the oxidation of Cu. In this paper, we propose a pulsed-current (PC) plating method to deposit nickel onto the Cu NWs in order to reduce oxidation over a 30-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In [20], the process of forming transparent conducting electrodes based on copper nanowires coated with nickel in pulsed modes was carried out. The group showed that different modes of pulsed deposition of nickel over a copper nanowire mesh significantly changed the characteristics of the resulting coating.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In [20], the process of forming transparent conducting electrodes based on copper nanowires coated with nickel in pulsed modes was carried out. The group showed that different modes of pulsed deposition of nickel over a copper nanowire mesh significantly changed the characteristics of the resulting coating.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The oxidation of Cu nanowires (NWs) in ambient conditions is a critical issue that has limited the usage of this material to commercial applications. Recently, Vuong et al proposed a Nickel coating process on Cu NWs to overcome this drawback [1]. First, the Cu NWs (55.3 ± 7.1 nm of diameter, over 100 µm of length) were synthesized via a hexadecylamine (HDA)-mediated method, then the pulsed electrode plating technique was used to form the Cu core-Ni shell on the polyethylene terephthalate (PET) film.…”
mentioning
confidence: 99%